Efeitos de diferentes estímulos auditivos musicais sobre a regulação autonômica cardíaca - Ferreira, Lucas Lima [UNESP] (2014)
Recently the literature has investigated the relationship between music and cardiovascular system including the autonomic nervous system (ANS). One way to assess the ANS is heart rate variability (HRV). This dissertation aimed to analyze the influence of musical auditory stimuli (ASM) on neurophysiological mechanisms, specifically on blood pressure (BP) and to analyze the effects of different ASM on the recovery response of cardiac autonomic control in women healthy. A review study was performed through the intersection of music descriptor with the descriptors for blood pressure and neurophysiology, in database MEDLINE, PEDro, SciELO and LILACS. An observational study conducted in 30 healthy women between 18 and 30 years old who underwent an experimental protocol of HRV analysis during 10 minutes at rest, 10 minutes of exposure to the classic style ASM (64-84 dB) and heavy metal (75-84 dB) and 30 minutes after cessation of ASM was performed. The following HRV indices were analyzed: SDNN (standard deviation of all normal RR intervals recorded at an interval of time), RMSSD (square of the average of the squared differences between adjacent normal RR intervals in a time interval root), pNN50 (percentage of adjacent RR intervals differing by duration longer than 50ms)...